Use of non-pharmacological interventions for comforting patients in palliative care: a scoping review - Coelho, Adriana Raquel Neves (2017)
Background Palliative care aims to provide the maximum possible comfort to people with advanced and incurable diseases. The use of non-pharmacological interventions to promote comfort in palliative care settings has been increasing. However, information on implemented and evaluated interventions, their characteristics, contexts of application, and population is scattered in the literature, hampering the formulation of accurate questions on the effectiveness of those interventions and, consequently, the development of a systematic review. Objective The objective of this scoping review is to examine and map the non-pharmacological interventions implemented and evaluated to provide comfort in palliative care. Inclusion criteria Types of participants This scoping review considered all studies that focused on patients with advanced and incurable diseases, aged 18 years or older, assisted by palliative care teams. Concept This scoping review considered all studies that addressed non-pharmacological interventions implemented and evaluated to provide comfort for patients with advanced and incurable diseases. It considered non-pharmacological interventions implemented to provide not only comfort but also well-being, and relief of pain, suffering, anxiety, depression, stress and fatigue which are comfort-related concepts. Context This scoping review considered all non-pharmacological interventions implemented and evaluated in the context of palliative care. This included home care, hospices or palliative care units (PCUs). Types of sources This scoping review considered quantitative and qualitative studies, and systematic reviews. Search strategy A three-step search strategy was undertaken: 1) an initial limited search of CINAHL and MEDLINE; 2) an extensive search using all identified keywords and index terms across all included databases; and 3) a hand search of the reference lists of included articles. This review was limited to studies published in English, Spanish and Portuguese in any year. Extraction of results A data extraction instrument was developed. Two reviewers extracted data independently. Any disagreements that arose between the reviewers were resolved through discussion, or with a third reviewer. When necessary, primary authors were contacted for further information/clarification of data. Presentation of results Eighteen studies were included covering 10 non-pharmacological interventions implemented and evaluated to provide comfort. The interventions included one to 14 sessions. The interventions lasted between five and 60 minutes. Most of the interventions were implemented in PCUs and hospice settings. Ten of the 18 interventions were implemented and evaluated exclusively in cancer patients. Conclusions Ten non-pharmacological interventions were identified, of which the most common were music therapy and massage therapy. Their characteristics differed significantly across interventions and even in the same intervention. They were mostly implemented in palliative care units and hospices, and in patients with a cancer diagnosis. These data raise questions for future primary studies and systematic reviews. Implications for research Future research should focus on the implementation of interventions not only with cancer patients but also with noncancer patients and patients receiving palliative care at home. Systematic reviews on the effect of massage therapy and music therapy should be conducted.